2008
DOI: 10.1063/1.2838333
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and fatigue behavior of Pb(Zr0.52Ti0.48)O3∕(Bi3.15Nd0.85)Ti3O12 bilayered thin films

Abstract: Bilayered ferroelectric thin films consisting of Pb(Zr0.52Ti0.48)O3 (PZT) and (Bi3.15Nd0.85)Ti3O12 (BNT) layers have been successfully fabricated via a synthesis route of combining sol-gel and rf sputtering. Both ferroelectric layers are well retained in both PZT/BNT and BNT/PZT bilayered films as suggested by x-ray diffraction and secondary ion mass spectroscopy analyses. Their ferroelectric and dielectric properties are largely dependent on the thicknesses of the constituent layers. An anomalous enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The dielectric behavior and resistivity are slightly changed after a high-frequency (1 MHz) fatigue. However, a big difference in dielectric and resistivity behavior was observed in a low frequency region after a low-frequency (100 kHz and 50 kHz) fatigue, and the large dielectric relaxation in a low frequency region indicates the involvement of more space charge after a low frequency fatigue, confirming that space charge is responsible for the "wake up" phenomenon [17,25,27,28]. Moreover, the resistivity in a low frequency region becomes lower with decreasing frequencies, indicating the increase of the defect concentration after fatigue.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…The dielectric behavior and resistivity are slightly changed after a high-frequency (1 MHz) fatigue. However, a big difference in dielectric and resistivity behavior was observed in a low frequency region after a low-frequency (100 kHz and 50 kHz) fatigue, and the large dielectric relaxation in a low frequency region indicates the involvement of more space charge after a low frequency fatigue, confirming that space charge is responsible for the "wake up" phenomenon [17,25,27,28]. Moreover, the resistivity in a low frequency region becomes lower with decreasing frequencies, indicating the increase of the defect concentration after fatigue.…”
Section: Introductionsupporting
confidence: 53%
“…The "wake up" peak is formed and is shifted to a lower switching cycle with a decrease in f from 100 kHz to 10 kHz. Such an unusual fatigue behavior in multilayers is related to the higher leakage current and the space charge [25,26]. In order to illuminate this "wake up" phenomenon, the dielectric and resistivity behavior before and after fatigue at different switching frequencies were measured for the compositionally graded thin film, as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous investigations have also shown that the presence of space charges at the interface of constituent layers can affect the electrical properties of BNT-based ferroelectric thin films. 21 While the ferroelectric behavior is affected by the space charges at the interface between BFO and BNT nanolayers, the enhanced magnetic behavior is apparently related to the well established crystallinity of BFO nanolayer and the strong ͑111͒ orientation, as a result of the presence of the bottom BNT nanolayer. For the observed improvement in fatigue resistance of the bilayered BFO/BNT thin film, the potential energy for accumulating defects at the interface during polarization switches is lower than that of the ferroelectric bulk or single layer thin film, which can give rise to additional resistance to ferroelectric fatigue.…”
mentioning
confidence: 99%
“…Novel multilayers consisting of different layers have been intensively investigated in attempts to find better materials or to improve the electrical properties, where the coupling and interaction among layers can significantly improve the functional properties of ferroelectric thin films . Researches on multilayered structures consisting of different ferroelectric materials has been extensively conducted .…”
Section: Introductionmentioning
confidence: 99%